Dynamic optimization of beer fermentation: Sensitivity analysis of attainable performance vs. product flavour constraints. (2nd November 2017) - Rodman, Alistair D.; Gerogiorgis, Dimitrios I.
Highlights: Explicit multi-objective dynamic optimization of beer fermentation is pursued for the first time. Ethanol production maximization and batch duration minimization are simultaneously pursued. The strong influence of flavour (ethyl acetate, diacetyl) constraints is quantitatively monitored. Initialisation (temperature profile) and time discretization affect solution quality considerably. Novel solutions of strong industrial promise are reported; trade-off visualisations are illustrated. Abstract: The declining alcohol industry in the UK and the concurrent surge in supply and variety of beer products has created extremely competitive environment for breweries, many of which are pursuing the benefits of process intensification and optimization. To gain insight into the brewing process, an investigation into the influence of by-product threshold levels on obtainable fermentation performance has been performed, by computing optimal operating temperature profiles for a range of constraint levels on by-product concentrations in the final product. The DynOpt software package has been used, converting the continuous control vector optimization problem into nonlinear programming (NLP) form via collocation on finite elements, which has then been solved with an interior point algorithm. This has been performed for increasing levels of time discretization, by means of a range of initializing solution profiles, for a wide spectrum of imposed by-product flavour constraints. Each by-product flavour threshold affects process performance in a unique way. Results indicate that the maximum allowable diacetyl concentration in the final product has very strong influence on batch duration, with lower limits requiring considerably longer batches. The maximum allowable ethyl acetate concentration is shown to dictate the attainable ethanol concentration, and lower limits adversely affect the desired high alcohol content in the final product.